Characterization of the risk of emergencies in transboundary areas of Ukraine - V. O. Kostenko (Aspekti Publìčnogo Upravlìnnâ, 2015)
The paper presents the main risks of manmade and natural emergences disasters in transboundary areas of Ukraine. It has been established that the level of potential threats and consequences of emergencies in adjacent areas remains quite high, and the mechanisms of public adminisration at the level of local executive authorities, local government authorities and specialized government institutions in Ukraine in addressing these issues are inadequate and require improvement. Based on the analysis results of existing threats and unresolved problems to date with overcoming the consequences of emergencies with potential transboundary spread we have proved the necessity of introduction of new management mechanisms in this area, namely, the creation of a unified public system of avoidance, precaution and prevention of emergencies to ensure security of transboundary areas based on the characterization of their risks that will facilitate expanding and deepening the cooperation of the European regions in Ukraine to ensure the current level of protection.